NUCLEAR ENERGY PRODUCTION IN JORDAN: OPPORTUNITIES AND THREATS - N. Beithou; Mohammed Abdelkader (European Scientific Journal, ESJ, 2015)
Energy and Water are two words that overburden the world policies and people lives. Its availability is essential for the development of nations and enhancement of their life standards. Jordan is a country that imports 98% of its energy from outside. The variation of the fuel prices and the instabilities in the region exhausted the country’s economy. Citizens are almost shouting from the high prices and the dramatic drop in the living standards. In this study, the nuclear energy production option is selected to be analyzed from its opportunities and threats to the country. It has been found that nuclear reactors are a must for countries which have a large population with few natural resources. Nuclear reactors are rarely exploding, but if it does; its radiation effects on people are full catastrophe. Nevertheless, Jordan has a large area per capita with a very high insolation; Jordan has a high potential of solar power plants construction in its different regions, which is a green save energy. This energy is capable of solving Jordan electric needs and put Jordan in the level of developed countries with high human development indices.